Dampak Proses Pembangunan Bendungan Sidan terhadap Sosial Ekonomi Masyarakat dan Lingkungan di Desa Buahan Kaja, Kabupaten Gianyar dan Desa Sidan, Kabupaten Badung - DEWI, AYU SUKA; ANTARA, MADE; YUDHARI, I DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022, 2022)
Impact of Sidan Dam Construction Process on Socio-Economic Community and Environment in Buahan Kaja Village, Gianyar Regency and Sidan Village, Badung Regency.  The construction of Sidan dam is a national strategic project stipulated under Presidential Regulation No. 56 of 2018. The purpose of this study is to identify social impacts, analyze economic impacts and estimate the environmental impact of the Sidan dam construction process. The research methods used in this study use quantitative and qualitative descriptive research. The process of building Sidan dam has no social impact on the community measured from 4 parameters consisting of social activities, land acquisition processes, the emergence of criminality and lifestyle changes. However, the process of building Sidan dam has a social impact on the community, measured from 3 other parameters consisting of communication between farmers, the usefulness of dam construction and payment of compensation. The process of building the Sidan dam has no economic impact on the community, measured from the parameters of increasing the selling price of agricultural commodities. However, the process of building Sidan dam has an economic impact measured from 4 other parameters consisting of income, land prices, property ownership and job additions. The Sidan dam construction process has no environmental impact measured from 3 parameters consisting of water and air pollution, environmental cleanliness and water quality and quantity. However, the Sidan dam construction process has an environmental impact measured from 3 other parameters consisting of loss of agricultural land, noise and road access around the agricultural area.